KEMAMPUAN GURU PPKn MELAKUKAN ASSESSMENT PEMBELAJARAN BERDASARKAN KURIKULUM 2013 - Sarkadi Sarkadi (Jurnal Ilmiah Mimbar Demokrasi, 2016)
ABSTRACT This study discusses how a teacher's ability PPKn in Jakarta conducting assessment of learning after the enactment of curriculum 2013. Assessment of learning may include learning to competence assessment attitudes, knowledge, and skills. The results showed that the ability of teachers PPKn in conducting assessment of learning is: The average score of assessment by teachers PPKn in Jakarta which is used as target schools on the competence of attitude is 87. The competence of knowledge is 100, and the skill competency is 92. Score is categorized as excellent (76-100). In other words, the ability of teachers PPKn in conducting assessment of learning (competence attitudes, knowledge, and skills) in Jakarta which is used as target schools categorized as excellent, Keywords: Education, teachers, civics education, learning assessment.